STRUKTURASI PENDIDIKAN INKLUSI PADA LINGKUNGAN HETEROGEN - Lussy Yuris Frasticha (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the structuration of inclusive education implementation within a heterogeneous environment and to understand the awareness of students with different abilities (difabel) following the receipt of inclusive education at SMA Negeri 1 Gedangan, Sidoarjo. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews using semi-structured guides and documentation from various secondary sources. The results indicate that the implementation of inclusive education at SMA Negeri 1 Gedangan has been optimized through several initiatives, including the adjustment of the regular curriculum by lowering the Minimum Completeness Criteria (KKM) for students with disabilities, the provision of Special Assistant Teachers (GPK), and the establishment of resource rooms. This practice forms an "inclusive culture," which is the outcome of the duality between agents (school, teachers, students) and structure (government policies and school regulations). From the perspective of Anthony Giddens' Structuration Theory, these social practices are influenced by the structural dimensions of significance, domination, and legitimation. Furthermore, the study finds that the educational process fosters "practical consciousness" in students with disabilities who can perform routine activities according to their abilities, while others exhibit "discursive consciousness" due to inconsistencies between their routines and their specific capabilities.